Determination of apremilast in rat plasma by UPLC–MS/MS in ESI-negative mode to avoid adduct ions formation. (July 2016) - Iqbal, Muzaffar; Ezzeldin, Essam; Al-Rashood, Sara TA; Imam, Faisal; Al-Rashood, Khalid A
Background: Quantification of target analyte by LC–MS/MS is sometimes hampering due to competitive adduct ions formation (sodium and/or ammonium) in positive ionization mode. A UPLC–MS/MS assay was developed for the determination of apremilast in rat plasma using ESI-negative mode to avoid adduct ions formation.Method & results: After extraction from plasma by ethyl acetate, analyte and IS were separated on Aquity BEH C18 column using acetonitrile-10 mM ammonium acetate (85:15) as mobile phase. The calibration curve was linear between 3.04 and 1000 ng/ml with correlation coefficients (r 2 ) of ≥0.995 and lower limit of quantification of 3.04 ng/ml. All validation parameter results were within the acceptable range. The assay was successfully employed in oral PK study with Cmax of 584.29 ng/ml and AUC0–20 of 6530 ng.h/ml after apremilast (2 mg/kg) administration.Conclusion: This result suggests that ESI in negative mode would be an alternative approach for LC–MS/MS quantification of analytes, which produce competitive adducts in positive mode.